SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Multi‐Species Telemetry Quantifies Current and Future Efficacy of a Remote Marine Protected Area - Morgan E. Gilmour; Kydd Pollock; Josh Adams; Barbara A. Block; Jennifer E. Caselle; Alex Filous; Alan M. Friedlander; Edward T. Game; Elliott L. Hazen; Marie Hill; Nick D. Holmes; Kevin D. Lafferty; et al. (Global Change Biology, 2025)
Large‐scale marine protected areas (LSMPAs; > 1000 km 2 ) provide important refuge for large mobile species, but most do not encompass species' ranges. To better understand current and future LSMPA value, we concurrently tracked nine species (seabirds, cetaceans, pelagic fishes, manta rays, reef sharks) at Palmyra Atoll and Kingman Reef (PKMPA) in the U.S. Pacific Islands Heritage Marine National Monument. PKMPA and the U.S. Exclusive Economic Zone encompassed 39% and 54% of species movements ( n = 83; tracking duration range: 0.5–350 days), respectively. Species distribution models indicated 73% of PKMPA contained highly suitable habitat. Under two projected future scenarios (SSP 1–2.6, “Sustainability”; SSP 3–7.0, “Rocky Road”), strong sea surface temperature gradients initially could cause abrupt oceanic change resulting in predicted habitat loss in 2040–2050, followed by an equilibrium response and regained habitat by 2090–2100. Current and future suitable habitats were available adjacent to PKMPA, suggesting that increased MPA size could enhance protection. Our three‐tiered approach combining animal tracking with publicly available remote sensing data and future projected environmental scenarios could be used to design, study, and monitor protected areas throughout the world. Holistic approaches that encompass diverse species and habitat use can enhance assessments of protected area designs. Animal telemetry and remote sensing may be helpful for ascertaining the extent to which other MPAs protect large mobile species in the future.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Re-assessing the age of the type locality of Nythosaurus larvatus (Therapsida, Cynodontia) and implications on the evolutionary dynamics of cynodonts - J. Benoit; S. Jirah; E.S. Lund; T. Lafferty; V. Buffa; L.A. Norton (Proceedings of the Geologists' Association, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Simultaneous improvement of grain yield and protein content in durum wheat by different phenotypic indices and genomic selection - M. Rapp; V. Lein; F. Lacoudre; J. Lafferty; E. Müller; G. Vida; V. Bozhanova; A. Ibraliu; P. Thorwarth; H. P. Piepho; W. L. Leiser; T. Würschum; et al. (Theoretical and Applied Genetics, 2018)

Host density increases parasite recruitment but decreases host risk in a snail–trematode system - J. C. Buck; R. F. Hechinger; A. C. Wood; T. E. Stewart; A. M. Kuris; K. D. Lafferty (Ecology, 2017)
Most species aggregate in local patches. High host density in patches increases contact rate between hosts and parasites, increasing parasite transmission success. At the same time, for environmentally transmitted parasites, high host density can decrease infection risk to individual hosts, because infective stages are divided among all hosts in a patch, leading to safety in numbers. We tested these predictions using the California horn snail, Cerithideopsis californica (= Cerithidea californica ), which is the first intermediate host for at least 19 digenean trematode species in California estuaries. Snails become infected by ingesting trematode eggs or through penetration by free‐swimming miracidia that hatch from trematode eggs deposited with final‐host (bird or mammal) feces. This complex life cycle decouples infective‐stage production from transmission, raising the possibility of an inverse relationship between host density and infection risk at local scales. In a field survey, higher snail density was associated with increased trematode (infected snail) density, but decreased trematode prevalence, consistent with either safety in numbers, parasitic castration, or both. To determine the extent to which safety in numbers drove the negative snail‐density–trematode‐prevalence association, we manipulated uninfected snail density in 83 cages at eight sites within Carpinteria Salt Marsh ( California , USA ). At each site, we quantified snail density and used data on final‐host (bird and raccoon) distributions to control for between‐site variation in infective‐stage supply. After three months, overall trematode infections per cage increased with snail biomass density. For egg‐transmitted trematodes, per‐snail infection risk decreased with snail biomass density in the cage and surrounding area, whereas per‐snail infection risk did not decrease for miracidium‐transmitted trematodes. Furthermore, both trematode recruitment and infection risk increased with infective‐stage input, but this was significant only for miracidium‐transmitted species. A model parameterized with our experimental results and snail densities from 524 field transects estimated that safety in numbers, when combined with patchy host density, halved per capita infection risk in this snail population. We conclude that, depending on transmission mode, host density can enhance parasite recruitment and reduce per capita infection risk.

Moose (Alces alces) hunters subsidize the scavenger community in Alaska - Diana J. R. Lafferty; Zachary G. Loman; Kevin S. White; Anita T. Morzillo; Jerrold L. Belant (Polar Biology, 2016)

How large is the hand in the puppet? Ecological and evolutionary factors affecting body mass of 15 trematode parasitic castrators in their snail host - Ryan F. Hechinger; Kevin D. Lafferty; Frank T. Mancini; Robert R. Warner; Armand M. Kuris (Evolutionary Ecology, 2009)

Parasites in food webs: the ultimate missing links - Kevin D. Lafferty; Stefano Allesina; Matias Arim; Cherie J. Briggs; Giulio De Leo; Andrew P. Dobson; Jennifer A. Dunne; Pieter T. J. Johnson; Armand M. Kuris; David J. Marcogliese; Neo D. Martinez; Jane Memmott; et al. (Ecology Letters, 2008)
Parasitism is the most common consumer strategy among organisms, yet only recently has there been a call for the inclusion of infectious disease agents in food webs. The value of this effort hinges on whether parasites affect food‐web properties. Increasing evidence suggests that parasites have the potential to uniquely alter food‐web topology in terms of chain length, connectance and robustness. In addition, parasites might affect food‐web stability, interaction strength and energy flow. Food‐web structure also affects infectious disease dynamics because parasites depend on the ecological networks in which they live. Empirically, incorporating parasites into food webs is straightforward. We may start with existing food webs and add parasites as nodes, or we may try to build food webs around systems for which we already have a good understanding of infectious processes. In the future, perhaps researchers will add parasites while they construct food webs. Less clear is how food‐web theory can accommodate parasites. This is a deep and central problem in theoretical biology and applied mathematics. For instance, is representing parasites with complex life cycles as a single node equivalent to representing other species with ontogenetic niche shifts as a single node? Can parasitism fit into fundamental frameworks such as the niche model? Can we integrate infectious disease models into the emerging field of dynamic food‐web modelling? Future progress will benefit from interdisciplinary collaborations between ecologists and infectious disease biologists.